Modeling and Design of Azimuth-Altitude Dual Axis Solar Tracker for Maximum Solar Energy Generation - Salem Alaraby Ali Shufat; Erol Kurt; Aybaba Hancerlioğulları (International Journal of Renewable Energy Development, 2019)
The sun tracking system that lets Parabolic Dish or PV panel orthogonal to the sun radiation during the day, can raise the concentrated sun radiation by up to 40%. The fixed Parabolic Dish cannot generally track the sun trajectory, also the single-axis tracking system can follow the sun in the horizontal direction (azimuth angle), while the two-axis tracker tracks the sun path in both azimuth and altitude angles. Dual axis automated control tracking system, which tracks the sun in two planes (azimuth and altitude) to move a Concentrated Parabolic Dish system to the direction of ray diffusion of sun radiation is studied and designed. The designed tracking system constructed of microcontroller or programmable logic control (PLC) with a digital program that operates sun tracker using driver, gear box to control the angular speed and mechanical torque, supports and mountings. Two steeper motors are modelled to guide the parabolic dish panel perpendicular to the sun's beam. In the present study, simulation scheme of two axis sun tracking system has been developed by operating under Matlab/Simulink. The program models and studies the effectiveness of overall system. The designed tracker has been studied with real data of sun trajectory angles (azimuth and altitude) as well as a Direct Normal Irradiation (DNI) to improve the effectiveness of parabolic dish panel by adding the tracking features to those systems according to the present site.©2019. CBIORE-IJRED. All rights reservedArticle History: Received May 18th 2018; Received in revised form October 8th 2018; Accepted January 6th 2019; Available onlineHow to Cite This Article: Shufat, S.A., Kurt, E, and Hancerlioğulları, A. (2019) Modeling and Design of Azimuth-Altitude Dual Axis Solar Tracker for Maximum Solar Energy Generation. Int. Journal of Renewable Energy Development, 8(1), 7-13.https://doi.org/10.14710/ijred.8.1.7-13